Patient-centered pharmacovigilance: priority actions from the inherited bleeding disorders community - Fiona Robinson; Sonji Wilkes; Nathan Schaefer; Miriam Goldstein; Michelle Rice; Johanna Gray; Sharon Meyers; Leonard A. Valentino (SAGE Publishing, 2023)
Pharmacovigilance, the science and practice of monitoring the effects of medicinals and their safety, is the responsibility of all stakeholders involved in the development, manufacture, regulation, distribution, prescription, and use of drugs and devices. The patient is the stakeholder most impacted by and the greatest source of information on safety issues. It is rare, however, for the patient to take a central role and exert leadership in the design and execution of pharmacovigilance. Patient organizations in the inherited bleeding disorders community are among the most established and empowered, particularly in the rare disorders. In this review, two of the largest bleeding disorders patient organizations, Hemophilia Federation of America (HFA) and National Hemophilia Foundation (NHF), offer insights into the priority actions required of all stakeholders to improve pharmacovigilance. The recent and ongoing increase in incidents raising safety concerns and a therapeutic landscape on the cusp of unprecedented expansion heighten the urgency of a recommitment to the primacy of patient safety and well-being in drug development and distribution. Plain Language Summary Patients at the center of product safety Every medical device and therapeutic product has potential benefits and harms. The pharmaceutical and biomedical companies that develop them must demonstrate that they are effective, and the safety risks are limited or manageable, for regulators to approve them for use and sale. After the product has been approved and people are using it in their daily lives, it is important to continue to collect information about any negative side effects or adverse events; this is called pharmacovigilance. Regulators, like the United States (US) Food and Drug Administration, the companies that sell and distribute the products, and healthcare professionals who prescribe them are all required to participate in collecting, reporting, analyzing, and communicating this information. The people with the most firsthand knowledge of the benefits and harms of the drug or device are the patients who use them. They have an important responsibility to learn how to recognize adverse events, how to report them, and to stay informed of any news about the product from the other partners in the pharmacovigilance network. Those partners have a crucial responsibility to provide clear, easy-to-understand information to patients about any new safety concerns that come to light. The community of people with inherited bleeding disorders has recently encountered problems with poor communication of product safety issues, prompting two large US patient organizations, National Hemophilia Foundation and Hemophilia Federation of America, to hold a Safety Summit with all the pharmacovigilance network partners. Together they developed recommendations to improve the collection and communication of information about product safety so that patients can make well-informed, timely decisions about their use of drugs and devices. This article presents these recommendations in the context of how pharmacovigilance is supposed to work and some of the challenges encountered by the community.